2020
DOI: 10.1186/s40621-020-00236-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of traumatic falls after Hurricane Maria in Puerto Rico

Abstract: Background: Hurricanes are among the most devastating natural disasters, playing a significant role in public health. Currently, the epidemiology of fall-related injuries after the occurrence of a tropical storm is not well described. This study aims to compare the demographical patterns, clinical profile, hospital course, and costs of patients admitted to the Puerto Rico Trauma Hospital before and after Hurricane Maria. Methods: A retrospective study was performed to compare fall-related injuries after the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…On 20 September 2017, Hurricane Maria (HM) made direct landfall south of Yabucoa Harbor in Puerto Rico (PR) as a strong Category 4 storm, resulting in catastrophic flash floods and island-wide devastation. , HM directly killed 64 people in PR with excess deaths estimated from 990 to 4645, destroyed over 90% of the electrical systems and 80% of the agricultural sectors, and left large areas without communication, water, and health care services, all of which resulted in an extremely slow posthurricane recovery. , Limited studies on the impact of HM have reported increasing rates of adverse physical and psychological health consequences (e.g., fall-related injuries, leptospirosis infection, anxiety, post-traumatic stress) and hurricane-exacerbated environmental effects including persistent hydrological disruption, deterioration of coastal water quality, increased air pollution, and disturbance of forest ecosystems. , However, little is known about the disruption of HM on drinking water quality that is critical to waterborne/water-related disease control and public health protection …”
Section: Introductionmentioning
confidence: 99%
“…On 20 September 2017, Hurricane Maria (HM) made direct landfall south of Yabucoa Harbor in Puerto Rico (PR) as a strong Category 4 storm, resulting in catastrophic flash floods and island-wide devastation. , HM directly killed 64 people in PR with excess deaths estimated from 990 to 4645, destroyed over 90% of the electrical systems and 80% of the agricultural sectors, and left large areas without communication, water, and health care services, all of which resulted in an extremely slow posthurricane recovery. , Limited studies on the impact of HM have reported increasing rates of adverse physical and psychological health consequences (e.g., fall-related injuries, leptospirosis infection, anxiety, post-traumatic stress) and hurricane-exacerbated environmental effects including persistent hydrological disruption, deterioration of coastal water quality, increased air pollution, and disturbance of forest ecosystems. , However, little is known about the disruption of HM on drinking water quality that is critical to waterborne/water-related disease control and public health protection …”
Section: Introductionmentioning
confidence: 99%
“…36 While previous research in Puerto Rico in the context of Hurricanes Irma and Maria has focused on mortality, injuries, mental health, and nutrition, results from this study demonstrate that there is also a need to evaluate and plan for chronic diseases in this context. [11][12][13][14][15][16]36,37 Understanding the impact that natural disasters, like hurricanes, exert on the health of populations with chronic conditions or those at high risk of developing NCDs will help inform further efforts. The information obtained from this study is useful to develop better preparedness strategies from a public health perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Equally as important as ensuring proper preparedness for sudden and deadly weather events is the maintenance of acute care and trauma surge capacity in the immediate time period after the natural disaster has passed. Previous studies have shown that certain categories of injuries can have a high incidence for weeks following natural disasters due to hazardous environmental conditions (Ramírez-Martínez et al, 2020). For example, the Task Force for Pediatric Emergency Mass Critical Care has made specific recommendations for hospitals endemic to disaster-prone areas to have three times the supplies and equipment above usual intensive care unit capacity in order to adequately manage pediatric surge patients for at least 10 days following natural disasters (Bohn et al, 2011).…”
Section: Discussionmentioning
confidence: 99%